Implementasi Pengolahan Sampah Organik Melalui Kegiatan Pembuatan Eco Enzym di TK Johar Baru Jakarta Pusat - Aryani, Rita; Mamba’usa’adah, Muna Sovia; Hariyani, Ade; El liza, Mona; Asmorowati, Murni Mei; Yati, Rosmidar; Barokah, Najjah (Civiliza Publishing, 2024)
The aim of this PKM activity is to create learning activities about organic waste processing that are interesting and fun for students through eco enzyme making activities which will be carried out from 20 October 2023 to 25 November 2023. This eco enzyme making activity goes through three stages, namely planning, implementation, and evaluation. The methods used at this planning stage are observation, interviews, and Focus Group Discussion (FGD). The implementation stages are carried out by implementing the Learning Implementation Plan (RPP) that has been created. The evaluation stage is carried out by reflecting on the plans that have been made and the implementation that has been carried out. The results of this activity show that there has been an increase in the knowledge of Johar Baru Kindergarten students and educators in Central Jakarta regarding the manufacture and benefits of eco-enzymes. Initially the problem at Johar Baru Kindergarten, Central Jakarta was the lack of use of used media and understanding of waste management and processing. This PKM activity has increased the knowledge of Johar Baru Kindergarten teachers and students in processing organic waste by making eco enzymes.